(untitled) (Journal of Pharma Insights and Research, 2023)
Bullous pemphigoid (BP) is an autoimmune disorder characterized by the development of fluid-filled blisters on the skin, and it is a rare but serious complication linked to specific medications, notably chemotherapeutic agents. This case details a 57-year-old female with stage-II cervical cancer who experienced widespread blistering lesions on her body after undergoing two cycles of chemotherapy involving paclitaxel and carboplatin. The patient noticed the appearance of multiple fluid-filled, reddish blisters on her hands, back, abdomen, and lower extremities, accompanied by a burning sensation, three days after the initial day of the latest chemotherapy session. Confirmatory histopathological and immunological assessments established the diagnosis of BP, an immune-mediated condition targeting the basement membrane zone through autoantibodies against bullous pemphigoid antigen-1 and antigen-2. The patient’s symptoms were successfully managed with corticosteroids, and the implicated chemotherapeutic agents were discontinued. This case underscores the crucial importance of monitoring cancer patients undergoing chemotherapy for cutaneous adverse reactions, especially those presenting with blistering eruptions. It highlights the necessity for prompt recognition and appropriate management of drug-induced bullous pemphigoid in such cases